CREATES - Convolutional Neural Network applied to Identification of Musical Elements in OMR - Barbosa, Jenaro Augusto; Santos, Edimilson Batista dos (Anais do Simpósio Brasileiro de Computação Musical (SBCM); 2021: Anais do XVIII Simpósio Brasileiro de Computação MusicalDO - 10.5753/sbcm.2021.19452, 2021)
Optical music recognition (OMR) is an important tool to recognize a scanned page of music sheet automatically, which has been applied to preserving music scores. In this paper, we present a comparative study among Convolutional Neural Network (CNN) and state-of-the-art classiers to classify musical symbols. The initial results show that the CNN is promising in this task according to provided information.